Conjunctival autograft transplantation for primary pterygium - Chaidaroon W. (2014)
Purpose: To evaluate the success rate of conjunctival autograft transplantation for primary pterygium. Material and Method: The results of 56 patients with primary pterygia who underwent conjunctival autograft transplantation were retrospectively reviewed. The success rate was evaluated in terms of recurrence percentage of pterygia onto the cornea. Results: Of the 56 patients, 20 were men and 36 women. The mean follow-up was 16.3 ± 8.2 months. Three (5%) eyes had recurrent pterygium within 1 year. No serious sight-threatening complications were associated with this study. Conclusion: Conjunctival autograft transplantation can achieve very low recurrence rates for primary pterygium and may be considered a safe procedure.